AGRO SAFARI (CIPEEX, 2024)
&NBSP;AGROSAFARI IS A WEB AND MOBILE APPLICATION DESIGNED TO INTEGRATE ESSENTIAL INFORMATION AND STREAMLINE AGRICULTURAL OPERATIONS MANAGEMENT, ACTING AS A MEDIATOR BETWEEN PRODUCERS AND SERVICE PROVIDERS IN THE AGRICULTURAL SECTOR. THE MAIN OBJECTIVE OF THIS PROJECT IS TO CREATE A DIGITAL PLATFORM THAT CENTRALIZES CRUCIAL INFORMATION FOR AGRICULTURAL PROFESSIONALS WHILE OFFERING A UNIQUE "MARKETPLACE" FUNCTIONALITY. THIS WILL ALLOW USERS TO ACCESS A DEDICATED SECTION FOR HIRING SERVICES, SIMPLIFYING THE MANAGEMENT AND CONTROL OF AGRICULTURAL OPERATIONS TO OPTIMIZE CROP DEVELOPMENT. THE APPLICATION WILL BE DEVELOPED TO OPERATE ON BOTH WEB AND MOBILE DEVICES, ENSURING ACCESSIBILITY AND CONVENIENCE FOR USERS IN DIFFERENT CONTEXTS. IT WILL INCORPORATE A WIDE RANGE OF RELEVANT AND INFORMATIVE INFORMATION RELATED TO THE AGRICULTURAL SECTOR, INCLUDING CROP DATA, AGRICULTURAL TECHNIQUES, WEATHER INFORMATION, AND MORE. ADDITIONALLY, THE "MARKETPLACE" FUNCTIONALITY WILL ENABLE FARMERS TO EASILY FIND AND HIRE SERVICE PROVIDERS SUCH AS AGRICULTURAL CONSULTANTS, SPRAYING COMPANIES, HARVESTING, AND TRANSPORTATION SERVICES. THE APPLICATION IS EXPECTED TO SIGNIFICANTLY CONTRIBUTE TO IMPROVING EFFICIENCY AND PRODUCTIVITY IN THE AGRICULTURAL SECTOR BY PROVIDING A SINGLE, RELIABLE SOURCE OF INFORMATION AND CONNECTING PRODUCERS WITH SPECIALIZED SERVICES. THIS CAN RESULT IN MORE SUCCESSFUL CROPS, REDUCED OPERATIONAL COSTS, AND BETTER UTILIZATION OF AVAILABLE RESOURCES. INFORMATION CENTRALIZATION AND THE ADDITION OF THE "MARKETPLACE" ARE KEY ELEMENTS THAT MAKE THIS APPLICATION UNIQUE AND VALUABLE FOR THE AGRICULTURAL SECTOR. THE ABILITY TO ACCESS RELEVANT INFORMATION AND EFFICIENTLY HIRE SERVICES CAN BENEFIT BOTH PRODUCERS AND SERVICE PROVIDERS, PROMOTING COLLABORATION AND GROWTH IN THE INDUSTRY. THIS PROJECT AIMS TO ENHANCE DECISION-MAKING AND AGRICULTURAL OPERATIONS MANAGEMENT, CONTRIBUTING TO MORE SUSTAINABLE AND PROFITABLE AGRICULTURAL DEVELOPMENT.&NBSP;
Keywords: AgroSafari; Agricultural management; Agricultural marketplace; Agricultural efficiency